Establishing CT-based reference ranges for liver and spleen sizes in the Pakistani pediatric population - Yousaf, Muhammad; Mirza, Waseem Akhtar; Sajjad, Mariam; Alam, Muhammad Masood; Aman, Muhammad; Zafar, Burhan; Rasheed, Aisha; Islam, Faizan UL; Hassan, Ayesha; Zafar, Kaleem Ahmad (International Journal of Pathology, 2025)
Background: Accurate liver and spleen reference ranges are essential for diagnosing pediatric abnormalities. Most existing data rely on ultrasound, while CT offers greater measurement precision, yet age-specific CT-based norms remain limited. This study aims to establish CT based reference values for liver and spleen sizes based on age, gender and anthropometric parameters in Pakistani pediatric population. Methods: This study analyzed CT scans of 772 children aged 0 to 16 years, selected from 7,000 records from January 2010 to December 2024 at Aga khan University hospital Karachi. The participants were grouped into 19 age categories ranging from 0-1 week to 15-16 years. At least four liver measurements and three spleen measurements were taken on axial and coronal images for every case. Mean and standard deviation were calculated, and variations between age groups and genders were evaluated. Results: Liver and spleen sizes increased significantly with age (p < 0.001). The mean liver anteroposterior (AP) diameter taken at mid-clavicular increased from 76.59 ± 15.25 mm in the youngest age group to 129.49 ± 14.05 mm in the older children. Similarly, the liver’s transverse diameter increased from 85.76 ± 22.03 mm to 154.14 ± 26.20 mm (p < 0.001). Spleen dimensions also displayed consistent age-dependent growth (p < 0.001). Although males had marginally higher mean values, the differences were statistically insignificant. Furthermore, height and BMI were found to be the strongest independent predictors overall through the regression analysis. Conclusion: Both liver and spleen dimensions showed a steady increase with age, with no significant differences between boys and girls. These CT-based reference ranges provide valuable benchmarks to distinguish normal organ growth from pathological enlargement in children.